The serum creatinine to cystatin C ratio predicts bone fracture in patients with type 2 diabetes: The Fukuoka Diabetes Registry. (December 2018) - Komorita, Yuji; Iwase, Masanori; Fujii, Hiroki; Ide, Hitoshi; Ohkuma, Toshiaki; Jodai-Kitamura, Tamaki; Sumi, Akiko; Yoshinari, Masahito; Nakamura, Udai; Kitazono, Takanari
Abstract: Aims: Sarcopenia is involved in the pathogenesis of increased fracture risk associated with diabetes. The serum creatinine to cystatin C (Cr/CysC) ratio has been reported as a surrogate marker for muscle mass. We aimed to prospectively investigate the relationship between the Cr/CysC ratio and fracture risk. Methods: We followed 1911 postmenopausal women and 2689 men with type 2 diabetes (mean age, 66 years) for a median of 5.3 years, and divided into Cr/CysC ratio quartiles by sex. The primary outcome was fragility fractures and the secondary outcome was any fracture. Results: Fragility fractures occurred in 192 participants, and any fracture occurred in 645 participants. Multivariate-adjusted hazard ratios (95% CI) for fragility fractures were 2.15 (1.19–3.88) (Q1), 1.63 (0.89–2.98) (Q2), 1.34 (0.72–2.51) (Q3) and 1.0 (ref.) (Q4) in postmenopausal women, and 1.75 (0.64–4.50) (Q1), 2.09 (0.83–5.26) (Q2), 1.56 (0.58–4.18) (Q3) and 1.0 (ref.) (Q4) in men. Those for any fracture were 1.46 (1.07–1.98) (Q1), 1.33 (0.98–1.81) (Q2), 1.40 (1.03–1.88) (Q3) and 1.0 (ref.) (Q4) in postmenopausal women, and 2.33 (1.54–3.54) (Q1), 2.02 (1.54–3.04) (Q2), 1.13 (0.71–1.78) (Q3) and 1.0 (ref.) (Q4) in men. Conclusions: A lower Cr/CysC ratio is a significant risk factor for fractures in patients with type 2 diabetes.